The business of champagne : a delicate balance - Charters, Stephen (New York ; London : Routledge, 2012)
"The world of champagne offers a fascinating insight into the complexity of modern business management and marketing. Champagne is at the same time a wine, a luxury product and a regional brand - it is tied to the place from which it comes, and can be made nowhere else. It therefore highlights a range of characteristics which make it interesting to the modern business world. This is the first book to offer a complete overview of the way in which champagne as a product is organized, managed and marketed. The book covers the entire range of issues surrounding the management of the champagne industry by reviewing the current context of champagne (structural, economic and legal), the role of 'place' (identity and terroir and tourism), marketing the 'myth' of champagne (image and competitive advantage) and the management of the industry (accountability, people and the territorial brand). The book brings together leading academics and examines the champagne region from multidisciplinary perspectives. Examining the champagne region provides insight into a range of management, production-management, branding and consumer-related issues and will be of interest to students, researchers and academics interested in Gastronomy, Wine Studies, Tourism, Hospitality, Marketing and Business"--
pt. 1. Context -- pt. 2. The place and the land -- pt. 3. Creating the myth and selling the wine -- pt. 4. Managing the industry -- pt. 5. Reflecting on champagne.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Wine industry -- France -- Champagne-Ardenne.; Champagne (Wine) -- Economic aspects; Wine and wine making; Wine industry; Electronic books